A new species of Mutinus (Phallaceae, Phallales) from Shandong Province, China - Zhou, Zhong-Liang; Li, Zhuang; Lyu, Yue; Liu, Ao; Gao, Yi-Ming; Wang, Pan-Meng (Phytotaxa, 2023)
A new species, Mutinus taishanensis (Phallaceae, Phallales, Basidiomycota), was found growing in a forest of Phyllostachys flexuosa and Quercus palustris in Zhulin Temple, Mount Tai Scenic Area (Tai’an City, Shangdong Province, China). It is described as new based on morphological, molecular and ecological evidence. Our phylogenetic analyses based on DNA sequences of the large subunit of nuclear ribosomal DNA (LSU), subunit 6 of ATP synthase (atp6) and the second largest subunit of RNA polymerase II (RPB2) support the inclusion of this new species in the genus Mutinus as it forms an independent clade in the phylogenetic tree. Morphologically, M. taishanensis differs from any known species by the combination of light red to red pseudostipe, red conical fertile portion (covering about 1/4–1/5 of the total length of pseudostipe), and relatively small basidiospores. We present this new species with illustrated morphological description. phylogeny and comparison with morphologically similar or phylogenetically related species.